Strategi Digital Public Relations untuk Meningkatkan Brand awareness di Brand Ekles Clinic Pluit Jakarta - Andriansyah, Ryan Rizky; Yonavilbia, Eka (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
The beauty industry in Indonesia is experiencing significant growth, with increasing public awareness of appearance and self-care. This research aimed to analyze the Digital Public Relations strategy used by Ekles Clinic in increasing brand awareness, identifying the obstacles faced, and finding solutions to those obstacles. The research method used was qualitative with a case study approach at the Ekles Clinic. Data was collected through in-depth interviews with relevant informants. The results showed that the Digital Public Relations strategy implemented by Ekles Clinic was effective in increasing brand awareness, but there were several obstacles such as tight competition and changes in consumer behavior that were increasingly digital-savvy. The advice given was to continue to innovate in digital communication strategies, increase interaction with audiences through social media, and utilize technology to monitor and evaluate campaign effectiveness